117k views
3 votes
Show that (2, 1) is a solution of the system of equations.

x + 3y = 5,
y = –x + 3

Substitute (2, 1) into x + 3y = 5 to get "Blank"
1+32=5
1+3(2) = 5
2+31 = 5
2+(3)=5
.
Simplify the equation to get "Blank"
5=5 is true
7=7 is true
7=5 is false
33=5 is false
.
Substitute (2, 1) into y = –x + 3 to get "Blank"
1= - (2)+3
1= - (2+3)
2= - (1) +3
2=-(1+3)
.
Simplify the equation to get "Blank"
1=1 is true
1 = - 1 is false
2 = 2 is true
2 = - 2 is false
.

User Ngoa
by
4.3k points

1 Answer

0 votes

Answer:

1) 2+(3)=5

2) 5=5 is true

3) 1=-(2)+3

4) 1=1 is true

Explanation:

User Omar Abdelrazik
by
4.7k points